2012
DOI: 10.1080/03079457.2012.709315
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress impairs performance and induces intestinal inflammation in broiler chickens infected withSalmonellaEnteritidis

Abstract: Stressful situations reduce the welfare, production indices and immune status of chickens. Salmonella spp. are a major zoonotic pathogens that annually cause over 1 billion infections worldwide. We therefore designed the current experiment to analyse the effects of 31±1°C heat stress (HS) (from 35 to 41 days) on performance parameters, Salmonella invasion and small intestine integrity in broiler chickens infected with Salmonella Enteritidis. We observed that HS decreased body weight gain and feed intake. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
129
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(141 citation statements)
references
References 55 publications
10
129
0
2
Order By: Relevance
“…The results obtained reinforce the hypothesis that the decreased performance observed in stressed broiler chickens might be related to alterations in the HPA axis function via corticosterone release (Shini & Kaiser, 2008;Shini et al, 2009;Quinteiro-Filho et al, 2010, 2012a, 2012b. Moreover, the observed intestinal inflammation could lead to a decrease in nutritional absorption because of the presence of intestinal lesions and because of sickness-related behaviour by release of certain interleukins (i.e.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The results obtained reinforce the hypothesis that the decreased performance observed in stressed broiler chickens might be related to alterations in the HPA axis function via corticosterone release (Shini & Kaiser, 2008;Shini et al, 2009;Quinteiro-Filho et al, 2010, 2012a, 2012b. Moreover, the observed intestinal inflammation could lead to a decrease in nutritional absorption because of the presence of intestinal lesions and because of sickness-related behaviour by release of certain interleukins (i.e.…”
Section: Discussionsupporting
confidence: 74%
“…Other results obtained in our laboratory revealed that different stressors such as footshock, chemical stressors and individual housing decreased the macrophage activity in mice (Fonseca et al, 2002;Palermo-Neto et al, 2003Quinteiro-Filho et al, 2009;Costa-Pinto & Palermo-Neto, 2010). In broiler chickens, we observed that heat stress decreased the macrophage oxidative burst (Quinteiro-Filho et al, 2010); this finding was linked to the observed increase of Salmonella migration to the spleen of heat-stressed chickens (Quinteiro-Filho et al, 2012a). In our study, overcrowding stress increased the Salmonella Enteritidis invasion to the liver but not to the spleen of the stressed chickens.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations